2021
DOI: 10.1007/s13304-021-01086-4
|View full text |Cite
|
Sign up to set email alerts
|

Congestive heart failure and comorbidity as determinants of colorectal cancer perioperative outcomes

Abstract: There has been an increase in surgical interventions in frailer elderly with concomitant chronic diseases. The purpose of this paper was to evaluate the impact of aging and comorbidities on outcomes in patients who underwent surgery for the treatment of colorectal cancer (CRC) in Veneto Region (Northeastern Italy). This is a retrospective cohort study in patients ≥ 40 years who underwent elective or urgent CRC surgical resection between January 2013 and December 2015. Independent variables included: age, sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although mortality is decreasing in the majority of developed countries, the number of deaths is estimated to increase by 60.0% for colon cancer and 71.5% for rectal cancer until 2035 [ 54 ]. Nevertheless, it is important to underline the increase in surgical interventions in frailer elderly affected by concomitant chronic diseases [ 55 , 56 ].…”
Section: Mortalitymentioning
confidence: 99%
“…Although mortality is decreasing in the majority of developed countries, the number of deaths is estimated to increase by 60.0% for colon cancer and 71.5% for rectal cancer until 2035 [ 54 ]. Nevertheless, it is important to underline the increase in surgical interventions in frailer elderly affected by concomitant chronic diseases [ 55 , 56 ].…”
Section: Mortalitymentioning
confidence: 99%
“…Therefore, with a longer life expectancy and an aging population, the number of patients with CRC and cardiovascular comorbidities is expected to increase ( 2 ). In a recent study, chronic heart failure (HF) was shown to increase the risk of 30-day mortality by up to 4-fold in patients with CRC undergoing colon resection ( 3 ).…”
Section: Introductionmentioning
confidence: 99%